Intelligent metering : trading : billing system IMTBS - Tian, Wentao. (2009)
Abstract Structure of Future Distribution System has changed lots due to the addition of Distributed Green Power Producers and the addition of power market in system operation. This requires fundamental modifications of the current energy meter to incorporate time-of-use metering, two-way metering, automatic billing and trading functions. To solve this problem, the Intelligent Metering/Trading/Billing System (IMTBS) is under development. A detailed analysis of the existing Intelligent Digital Meter (IDM) based on ADE7756 in this IMTBS is made in terms of both its advantages and limitations. A more intelligent IDM based on ADE7169 is outlined in this report as a better option in energy metering. During this FYP period, I did some experiments and analyzed the different energy meter ICs, then designed the new IDM based on ADE7756. For the limitation of time, the design was not accomplished. I would hope the next batch will be handing this. The focus of the report is mainly laid on introducing the working principle and analyzing the reliability of the system in data processing and the efficiency of the communication. Also, the design of the proposed IDM based on ADE7169 is covered in this document.